Insolation forcing of coccolithophore productivity in the North Atlantic during the Middle Pleistocene - Cavaleiro, Catarina; Voelker, Antje H.L.; Stoll, Heather; Baumann, Karl-Heinz; Kulhanek, Denise K.; Naafs, Bernhard D.A.; Stein, Ruediger; Grützner, Jens; Ventura, C.; Kucera, Michal (Quaternary Science Reviews, 2018)
ISSN:0277-3791